Global virtual teams performance measuring model for global software development projects - Gheni, Ali Yahya (2017)
Global virtual teams (GVTs) comprise team members who are geographically dispersed, culturally varied and mainly depend on information and communication technology (ICT) for communication. Despite the advancement of technology, achieving the efficient performance of GVTs remains a challenge. The reviewed literature has highlighted the importance of training and development, organizational commitment and motivation in enhancing the performance of these teams. However, previous studies have shown that the measurement of GVT performance is lacking in terms of online training and development, organizational commitment, and motivation. Therefore, this study aims to identify the main challenges encountered by GVTs in global software development (GSD) projects; examine the relationship among online training and development, organizational commitment, motivation, and performance of GVTs in GSD projects; and propose a model. A literature review was conducted, and the conceptual model was delivered to achieve the research objectives. Subsequently, a confirmation study that included an expert review, pilot study and survey were conducted among 103 respondents. Then, the performance measurement model (PMM) for GVTs in GSD projects was proposed based on the result of the confirmation study. Finally, a prototype was developed based on the proposed model. This prototype was validated through a survey conducted among developers and project managers. The proposed PMM includes four major components, namely, performance measurement processes, mapping strategy for performance evaluation, measurements and performance analysis. Finally, the PMM was verified by experts. The result of the confirmation study showed the validity and reliability of the proposed model. The validity of the prototype was confirmed by project managers in IT companies. The result of the expert review confirmed that the PMM can assist project managers in measuring the performance of GVTs in GSD Projects.